Creation of personal websites of teachers and their use in teaching latin language for special purposes in the higher school - E A Provotorova (RUDN Journal of Informatization in Education, 2013)
This article is devoted to introduction of modern information technologies in the process of teaching the Latin language to the students of higher educational institutions. The main attention is paid to the use in the course the Internet-technologies, in particular — personal sites of teachers.